The unusual canangafruticosides A-E: Five monoterpene glucosides, two monoterpenes and a monoterpene glucoside diester of the aryldihydronaphthalene lignan dicarboxylic acid from leaves of Cananga odorata var. fruticosa - Nagashima J. (2014)
From the leaves of Cananga odorata var. fruticosa, five unusual monoterpene glucosides, named canangafruticosides A-E (1-5), along with two unusual non-glucosidic monoterpenes (6, 7) were isolated. An aryldihydronaphthalene-type lignan dicarboxylate (8) was also isolated, with two moles of canangafruticoside A (1) on its ester moiety. This lignan also showed strong blue fluorescence emission under basic conditions. The structures of these compounds were elucidated by means of spectroscopic methods, with their absolute configurations determined by application of the modified Mosher's method to a compound chemically derived from canangafruticoside E. © 2010 Elsevier Ltd.